Exposure, sensitivity, or adaptive capacity? Reviewing assessments that use only two of three elements of climate change vulnerability - Amanda A. Hyman; Erin R. Crone; Abigail Benson; Jason Dunham; Abigail J. Lynch; Laura Thompson; Meryl C. Mims (Conservation Science and Practice)
Abstract As climate change accelerates, understanding which species are most vulnerable and why they are vulnerable will be vital to inform conservation action. Climate change vulnerability assessments (CCVAs) are tools to assess species' responses to climate change, detect drivers of vulnerability, and inform conservation planning. CCVAs are commonly composed of three elements: exposure, sensitivity, and adaptive capacity. Incorporating all three elements can be challenging, and including only two of the three elements may be a more feasible approach in many systems. Although two‐element CCVA approaches have become more common, their utility and procedures remain poorly documented. We conducted a literature review to explore the scope, methods, and rationale of CCVAs that use a two‐element approach to assess vertebrate vulnerability. Despite the potential to expand CCVAs into understudied systems, two‐element assessments had similar geographic and taxonomic biases as those previously detected in CCVAs in general. Methods varied, yet we found that variables used in two‐element studies could be condensed into standardized categories to enhance comparability. Finally, limitations in data availability and computational resources were common rationales for using a two‐element approach. By clarifying the purposes, opportunities, and limitations of two‐element assessment, this review can aid in selecting appropriate methods for CCVAs.